TrackMate 7: integrating state-of-the-art segmentation algorithms into tracking pipelines - Ershov, Dmitry; Phan, Minh-Son; Pylvänäinen, Joanna W.; Rigaud, Stéphane U.; Le Blanc, Laure; Charles-Orszag, Arthur; Conway, James R. W.; Laine, Romain F.; Roy, Nathan H.; Bonazzi, Daria; Duménil, Guillaume; Jacquemet, Guillaume; et al. (Nature methods, 2022)
TrackMate is an automated tracking software used to analyze bioimages and is distributed as a Fiji plugin. Here, we introduce a new version of TrackMate. TrackMate 7 is built to address the broad spectrum of modern challenges researchers face by integrating state-of-the-art segmentation algorithms into tracking pipelines. We illustrate qualitatively and quantitatively that these new capabilities function effectively across a wide range of bio-imaging experiments. TrackMate 7 combines the benefits of machine and deep learning-based image segmentation with accurate object tracking to enable improved 2D and 3D tracking of diverse objects in biological research.